10 dB reduction of drop operations of DSP-enabled soft-ROADMs for coherent systems - Jin, W.; Zhang, X.L.; Duan, X.; Dong, Y.X.; Giddings, R.P.; Qiu, K.; Zhang, C.F.; Tang, J.M. (Optics communications, 2018)
Newly proposed DSP-enabled ROADMs free from O−E−O conversions offer an excellent opportunity of utilising advanced DSP techniques to greatly simplify complicated conventional ROADM configurations, to introduce more highly desired networking functionalities and to create a programmable environment capable of addressing elastic 5G slicing and supporting the SDN paradigm. In this paper, detailed analytical and numerical investigations are performed, for the first time, of DSP-enabled ROADM drop operation performances in coherent systems. Two simple but effective drop operation approaches are proposed analytically and validated numerically, which, compared to the previously published quadrature-point-biased Mach–Zehnder modulator-based ROADM drop element subject to a standard drop RF signal, can not only improve the minimum required OSNR requirements by approximately 10 dB, but also considerably enhance the drop operation performance robustness to modulation index variations.